The phenomenon of public islam within urban da’wah practices in Bandung - Dudy Imanuddin Effendi; Dede Irawan; Lilim Abdul Halim (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2026)
Purpose - This study aims to explain how the phenomenon of public Islam is manifested within urban da’wah practices by examining the dynamics of da’wah spaces, the transformation of religious authority, and the emerging orientation toward public welfare in urban life Method - Using a phenomenological approach, this study examines the lived experiences of informants involved in urban da’wah, both as preachers and as audiences Result - Urban da’wah is increasingly moving beyond traditional places of worship into more fluid public spaces. This spatial expansion goes hand in hand with the strengthening of democratized religious authority, where legitimacy is shaped by the relevance of the message and its resonance with the lived experiences of urban communities. The findings also indicate a strong orientation toward public welfare, reflected in social initiatives, the avoidance of sensitive themes, and efforts to maintain social harmony within the city’s diverse environment. Implication – These findings imply the need to redefine da’wah concepts to become more responsive to urban social ecologies and adaptive to contemporary modes of public communication. Originality/Value - Its originality lies in combining phenomenology with the public Islam framework to conceptualize urban da’wah as a multisited, dialogical, and welfare-oriented practice, offering fresh insights for developing contemporary da’wah theory. *** Tujuan – Penelitian ini bertujuan menjelaskan bagaimana fenomena Islam publik termanifestasi dalam praktik dakwah urban dengan menelaah dinamika ruang dakwah, transformasi otoritas keagamaan, dan munculnya orientasi kemaslahatan dalam kehidupan masyarakat kota. Metode – Dengan menggunakan pendekatan fenomenologis, penelitian ini mengkaji pengalaman hidup para informan yang terlibat dalam dakwah urban, baik sebagai pendakwah maupun sebagai audiens. Hasil – Dakwah urban semakin bergerak melampaui tempat ibadah tradisional menuju ruang-ruang publik yang lebih cair. Perluasan ruang ini berjalan seiring menguatnya otoritas keagamaan yang semakin demokratis, di mana legitimasi dibentuk oleh relevansi pesan dan kedekatannya dengan pengalaman hidup masyarakat urban. Temuan penelitian juga memperlihatkan orientasi yang kuat terhadap kemaslahatan publik, tercermin dalam berbagai inisiatif sosial, penghindaran tema-tema sensitif, serta upaya menjaga harmoni sosial di tengah keberagaman kota. Implikasi – Temuan ini menunjukkan perlunya redefinisi konsep dakwah agar lebih responsif terhadap ekologi sosial perkotaan dan lebih adaptif terhadap pola komunikasi publik kontemporer. Orisinalitas/Nilai – Keaslian penelitian ini terletak pada integrasi pendekatan fenomenologi dengan kerangka Islam publik untuk mengonseptualisasikan dakwah urban sebagai praktik multisitus, dialogis, dan berorientasi kemaslahatan, sehingga menawarkan perspektif baru dalam pengembangan teori dakwah masa kini.